Edward Bond Bondian Drama and Young Audience - Ada, Ugur; Ada, Ugur (Vernon Press, 2023)
'Edward Bond: Bondian Drama and Young Audience' focuses on one of the most influential playwrights of Britain, Edward Bond, and his plays for young audiences. The chapters examine the theatrical and pedagogical prospects of the plays on young people which have been mostly staged since 1990s, throughout the globe.The issues covered in this book involve interdisciplinary studies such as theatre, pedagogy, ethics, children, culture, politics, among others. These topics have crucial importance for the production of plays for young audiences. Apart from this, the book focuses on Bondian Drama and its relation with the dramatic child, involving most of his plays for young audiences. The authors in this volume examine theatrical and pedagogical backgrounds of the plays, discussing critical issues, by questioning the specialities of Bondian drama and present future implications of this for young audiences. This volume presents substantial and elaborate information on crucial issues, and enable detailed discussions from various perspectives on theatre.